Effects of 15-year vegetation restoration on organic carbon in soil aggregates on the Loess Plateau, China. Issue 3 (23rd February 2023) - Shi, Peng; Ren, Mingxing; Li, Peng; Li, Zhanbin; Sun, Jingmei; Min, Zhiqiang; Ding, Shijie
ABSTRACT: Effects of 15-year vegetation restoration on organic carbon content of soil aggregates in the Wangmaogou Watershed in China were evaluated. Major land use types include grassland, forestland, shrubland, and sloping cropland. Soils from depths of 0–20, 20–40, and 40–60 cm were collected from each study site. Soil aggregates were divided into macro (5–2 mm), small (2–0.25 mm), and micro (< 0.25 mm) aggregates. Vegetation restoration improved the organic carbon content of soil aggregates, which was positively correlated with soil aggregate stability ( R = 0.44 and 0.53 for the mean weight diameter and geometric mean diameter, respectively) and negatively correlated ( R = – 0.57) with the soil erosion rate (measured by 137 Cs tracer). The levels of macro- and small- aggregates in vegetated lands were more than double than those in sloping cropland. Following vegetation restoration, the dominant soil aggregates in the 0–20 cm soil layer were transformed from micro-aggregates to macro-aggregates. The mean weight diameter and geometric mean diameter of soil aggregates from vegetated land were significantly higher than those of sloping cropland. Vegetation restoration increased the organic carbon content of soil aggregates by improving the stability of soil aggregates and reducing soil erosion.